1787 Mass. Acts 555 - (:unkn) unknown (My University, 1787)
Act of Feb. 16, 1787, ch. VI: Required persons against the Government to deliver their arms to a justice of the peace and "subscribe the oath of allegiance to this Commonwealth."
Keywords: POSSESSION - DANGEROUS PERSONS; LOYALTY OATH REQUIRED